Are Forensic Experts Biased by the Side That Retained Them? - Murrie, Daniel C.; Boccaccini, Marcus T.; Guarnera, Lucy A.; Rufino, Katrina A. (Psychological science, 2013)
How objective are forensic experts when they are retained by one of the opposing sides in an adversarial legal proceeding? Despite long-standing concerns from within the legal system, little is known about whether experts can provide opinions unbiased by the side that retained them. In this experiment, we paid 108 forensic psychologists and psychiatrists to review the same offender case files, but deceived some to believe that they were consulting for the defense and some to believe that they were consulting for the prosecution. Participants scored each offender on two commonly used, well-researched risk-assessment instruments. Those who believed they were working for the prosecution tended to assign higher risk scores to offenders, whereas those who believed they were working for the defense tended to assign lower risk scores to the same offenders; the effect sizes (d) ranged up to 0.85. The results provide strong evidence of an allegiance effect among some forensic experts in adversarial legal proceedings.